Clinical efficacy of early microsurgical clipping of tumor neck in the treatment of cerebral aneurysm rupture and bleeding and its impact on oxidative stress response and prognosis of patients: Early microsurgical clipping in cerebral aneurysm rupture - Chen, Zhenglou; Wang, Hongsheng; Xu, Min; Wang, Yunjiang; Hu, Xuqi (Cellular and Molecular Biology, 2024)
Cerebral aneurysm can rupture a blood vessel and cause bleeding in the brain. Microsurgical clipping of the tumor neck has been reported to be effective in treating cerebral aneurysm rupture and bleeding. This research attempted to clarify the clinical efficacy of early microsurgical clipping of tumor neck for treating cerebral aneurysm rupture and bleeding, and its impact on the prognosis of patients. One hundred patients with cerebral aneurysm rupture and bleeding patients were treated. They were selected and divided into experimental group (n=25) and control group (n=25) according to surgical time. All patients underwent microsurgical clipping of tumor neck for therapy. The control group chose to undergo surgery 72 hours after the onset of cerebral aneurysm rupture and bleeding, while the experimental group chose to undergo complete surgery within 72 hours after the onset of cerebral aneurysm rupture and bleeding. Primary outcome measures were incidence of complications, cognitive function scores, prognosis, surgical indicators, oxidative stress response and quality of life. Results showed that compared to the control group, the incidence of complications in experimental group exhibited depletion (P<0.05), the prognosis in experimental group exhibited elevation (P<0.05), the hospitalization time in experimental group exhibited depletion (P<0.05), the nomination, abstraction, language, orientation, attention, delayed recall and visual and executive function scores and total scores in experimental group exhibited elevation (P<0.05), serum levels of oxidative stress-related indicators in experimental group exhibited depletion (P<0.05) and the quality of life in experimental group exhibited elevation (P<0.05). In conclusion, early microsurgical clipping of the tumor neck can reduce the risk of complications and cognitive impairment in patients with cerebral aneurysm rupture and bleeding.